Formulation And Evaluation of Sunscreen Lotion Incorporated with Centella Asiatica Extracts - Sarbani, Nur Arina Filza binti; Mohamed, Elizah binti (Progress in Engineering Application and Technology, 2023)
The compounds that exist in the sunscreens nowadays have come in some health effects like rashes, acne, crusted rashes and in order to tackle these side effects, natural or herbal sunscreens comprising of organic material are made. This research aims to get the right sunscreen formulation incorporated with Gotu Kola or Centella asiatica extract in sunscreen, understanding the physicochemical characteristics, and acquire information about the formulations that has been produced by evaluating its physicochemical properties, SPF value, blocking ability, antimicrobial and antioxidant activity. In this study, preparation of sunscreen base and incorporation of C. asiatica extract was conducted to produce the formulated sunscreen, followed with its evaluation tests, which involves DPPH assay for antioxidant and Disc Diffusion method for antimicrobial testing. Sunscreen with formulation F20 (incorporated with 20% of C. asiatica extract) was seen to have a stable pH value of 7.25 ± 0.012. Next, the sunscreens were evaluated using SPF analysis. F20 produced has a maximum SPF value of 22.21. To evaluate the sunscreen properties, the ability of sunscreen to block UV light to microbes, Antioxidant and Antimicrobial activity of sunscreen was done. The blocking ability of sunscreens tested shows that F20 was able to block UV light from damaging E. Coli bacteria. The inhibition zone of the herbal sunscreen containing C. asiatica with 20% concentration is the highest which is 16mm at 100% concentration. The study showed that increasing C. asiatica extract led to a better result in the antioxidant activity in DPPH radical scavenging assay. The data shows suggests that sunscreen F20 formulated with 20% concentration of C. asiatica extract is suitable to be produced and commercialized.